Deletion of the Mir-106b~ 25 MicroRNA cluster attenuates atherosclerosis in Apolipoprotein E knockout mice - Jonathan Semo; Gil Chernin; Michael Jonas; Sara Shimoni; Jacob George (Lipids in Health and Disease, 2019)
Abstract Background MicroRNAs are short non-coding RNAs that regulate gene expression. The aim of this study was to gain an understanding of the possible role of the miR-106b~ 25 microRNA cluster in regulating atherosclerosis in mice. Methods MiR-106b~ 25 knockout mice were outcrossed into Apolipoprotein E (ApoE) knockout background to generate double knockout mice. At 36 weeks of age, lesion size was evaluated in the aortic sinus by oil-red-O staining. Results Lesion size was 2-fold smaller in double KO mice in comparison to ApoE KO mice. In addition, collagen staining showed a trend towards a stable plaque phenotype in the double KO mice. Lipid profiling of plasma samples of double KO and ApoE KO mice using FPLC revealed over 2-fold decrease in Very low density lipoprotein (VLDL) cholesterol content and a 50% decrease in low density lipoprotein (LDL) cholesterol content in double KO mice. By using target prediction software, we have identified several possible targets for the miR-106b~ 25 cluster including the VLDL and LDL receptors. We found that upon feeding miR-106b~ 25 KO mice with high fat diet, the expression of LDL and VLDL receptors was higher than in the wild-type mice, suggesting the miR-106b~ 25 cluster regulates atherosclerosis by influencing clearance of VLDL and LDL from the plasma. Conclusions We identified the miR-106b~ 25 cluster as a novel regulator of atherosclerosis in ApoE KO mice, presumably by regulating plasma cholesterol levels.